Does therapeutic hypothermia reduce acute kidney injury among term neonates with perinatal asphyxia? – a randomized controlled trial. (2nd August 2016) - Tanigasalam, Vasanthan; Bhat, Vishnu; Adhisivam, Bethou; Sridhar, M. G.
Abstract: Objective : The objective of this study is to evaluate whether therapeutic hypothermia reduces the incidence of acute kidney injury (AKI) among term neonates perinatal asphyxia. Methods : This randomized controlled trial conducted in a tertiary care teaching hospital, south India included 120 term neonates with perinatal asphyxia who were randomized to receive either therapeutic hypothermia or standard supportive care. Renal parameters of neonates in both the groups were monitored and AKI was ascertained as per Acute Kidney Injury Network criteria. Results : The incidence of AKI was less in therapeutic hypothermia group compared to standard treatment group (32% versus 60%, p  < 0.05). The incidence of Stages 1, 2, and 3 AKI was 22%, 5%, and 5% in therapeutic hypothermia group compared with 52%, 5%, and 3%, respectively, in the standard treatment group. The mortality was less in therapeutic hypothermia group compared with the standard treatment group (26% versus 50%, p  < 0.05). Conclusion : Therapeutic hypothermia reduces the incidence and severity of AKI among term neonates with perinatal asphyxia.